Pengaruh Perceived Entertainment, Celebrity Effect, Dan Perceived Usefulness di Platform E-commerce terhadap Dorongan Impulsive Buying melalui Attitude Toward Influencer Ads pada Generasi Z di Kota Surakarta - Riski Samsiyani; Aniek Hindrayani (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine: (1) the effect of live streaming on Generation Z’s purchasing decisions for local skincare products in Surakarta, (2) the effect of influencer marketing on purchasing decisions, (3) the effect of flash sales on purchasing decisions, and (4) the indirect effects of these variables through purchase intention. The population consists of Generation Z in Surakarta aged 15–This study aims to determine the effect of attitude toward influencer ads on Impulsive Buying; to determine the influence of celebrity effect, influencer credibility, Perceived Entertainment, Perceived Usefulness, and trust on attitude toward influencer ads; to determine the influence of influencer credibility on celebrity effect; to determine the influence of trust on Perceived Usefulness; to determine the influence of attitude toward influencer ads on Perceived Entertainment on Impulsive Buying; to determine the influence of celebrity effect and attitude toward influencer ads on influencer credibility on Impulsive Buying; and to determine the influence of Perceived Usefulness and attitude toward influencer ads on trust on Impulsive Buying. This is a descriptive quantitative study using primary data collection methods obtained from online questionnaires. The population used in this study was Generation Z in Surakarta City. The sampling technique used purposive sampling, resulting in a sample of 398 Generation Z consumers. Data analysis used Partial Least Squares (SEM-PLS) data analysis using the Smartpls 4.0 program. The results of the study indicate a positive and significant effect of attitude toward influencer ads on Impulsive Buying. There are positive and significant effects of celebrity effect, influencer credibility, Perceived Entertainment, Perceived Usefulness, and trust on attitude toward influencer ads. There is a positive and significant effect of influence credibility on celebrity effect. There is a positive and significant effect of trust on Perceived Usefulness. There is a positive and significant effect of attitude toward influencer ads mediating Perceived Entertainment on Impulsive Buying. There is a positive and significant effect of celebrity effect and attitude toward influencer ads mediating influencer credibility on Impulsive Buying. There is a positive and significant effect of Perceived Usefulness and attitude toward influencer ads mediating trust on Impulsive Buying. Keywords: Entertainment, Celebrity, Usefulness, Credibility, Trust